Analysis of drying characteristic, effective moisture diffusivity and energy, exergy and environment performance indicators during thin layer drying of tea in a convective-hot air dryer - Zeng, Zhiheng; Han, Chongyang; Wang, Qi; Yuan, Huilin; Zhang, Xuefeng; Li, Bin (Frontiers in Sustainable Food Systems, 2024)
The objective of this paper is mainly to analyze the drying kinetic parameters, effective diffusivity, and thermodynamic performance indicators (energy, exergy, heat, and mass transfer coefficients) of tea under different drying conditions of different drying temperatures (DT) and thin layer thicknesses (TT). Experimental drying was conducted at drying temperatures of 70 •C, 80 •C, and 90 •C with thin layer thicknesses of 10 mm, 15 mm, and 20 mm. The results show that a higher drying temperature and a lower thin layer thickness can increase evaporation moisture content and shorten drying time. By evaluating and comparing the fitting of five drying models adopted by the coefficient of determination (R 2 ) and Chi-Square (χ 2 ), it can be found that the logarithmic model was the best to describe drying behavior. The effective moisture diffusivity shows a positively correlated trend with the increase of DT and TT, with the value of activation energy ranging from 14.030 to 22.344 kJ mol -1 •K -1 . The specific moisture evaporation rate (SMER), energy efficiency, exergy efficiency, and sustainability index (SI) descend as the TT increases at all DT, the specific energy consumption (SEC) and improvement potential rate (IP) perform oppositely, but the TT remains unchanging. The conclusion drawn from the thermodynamic parameters mentioned above is opposite to the aforementioned. As the TT increases, the heat and mass transfer coefficients show a significant decrease trend. In addition, the heat and mass transfer coefficients are given as functions of DT and TT, and further knowledge shows that the mass transfer coefficient is positively correlated with DT but the heat transfer coefficient is negatively correlated. The study's findings can serve as a reference for tea's thin-layer drying technique.